Forecasting temperature and precipitation values over the coming decades using the canESM2 model In the Ahrchai watershed. - jaefar derakhshi; behroz sobhani; saeed jahanbakhsh (تحقیقات کاربردی علوم جغرافیایی)
In this study, the prediction of precipitation and temperature values using the general atmospheric circulation models during 1964-2005 is investigated. Climatic data including daily values of total precipitation and mean temperature were obtained from the Iranian Meteorological Organization. Considering the climate change scenarios RCP4.5, RCP2.6 and RCP8.5 for the coming period 2010-2100 were evaluated under the canESM2 climate change model of Aharchai Basin. Due to the low accuracy of the general circulation models, the SDSM4.2 miniaturization model was used and the changes in precipitation and mean temperature parameters were simulated for future time periods. In this study, to calibrate the SDSM model, among the 26 large scale climate parameters (NCEP), on average, 3 parameters have the highest correlation with the mean temperature and 5 parameters have the highest correlation with the average precipitation in the Aharchai Basin. The results of climatic parameters prediction showed that simulation of climatic parameters mean temperature was performed with higher accuracy than mean precipitation values. The reason is that the precipitation data are not normal and unconditional. The results show that the basin temperature averaged more during the period 2070-2099 under the scenario RCP8.5 than the observations period of 1964-2005 and the basin precipitation during the period 2070-2099 under the scenario RCP2.6 showed the highest increase in the entire study period.